Knowledge Management and the Practice of Storytelling : the Competencies and Skills Needed for a Successful Implementation. - Brown-Grant, Johel (Emerald Publishing Limited, 2022)
Knowledge Management and the Practice of Storytellingoffers practical advice and guidance on the skills and competencies needed to fully discover the power of storytelling to transform and transfer knowledge, and harness that power to meet business goal increases.